Experimental investigation on the behavior of corrugated steel shear wall subjected to the different angle of trapezoidal plate. (10th July 2017) - Hosseinzadeh, Leila; Emami, Fereshteh; Mofid, Masood
Summary: Studies on corrugated steel shear walls (CSSWs) generally indicate noticeable increase of energy absorption, as well as increasing shear buckling capacity of corrugated plates being more likely rather than the flat plates. In this paper, the effect of variation in the angle of trapezoidal plate on the behavior of CSSWs has extensively been investigated. Three specimens of CSSW with 1 story and single bay in half scale are tested under cyclic load. The observations of experiment do indicate that stress concentration has been increased in the corner of subpanels, by increasing of the corrugation angle. Development of the tensile field and wall yield and damage depends on the geometry of the plate. By increasing the corrugation angle, the stiffness and energy dissipation decrease; in addition, large loss of strength takes place. Comparing the numerical and experimental results indicates that for a closer look at behavior of trapezoidal CSSWs, fracture mechanics, fatigue, and damping of materials should be considered by numerical analysis.